Quality Cost Calculation as Data Source for Kaizen Costing System - Jozef GRUSZKA; Beata MRUGALSKA (Communications of International Proceedings, 2020)
The automotive industry sets new standards not only for quality management (ISO/TS 16949:2016) but it also inspires to search for effective production methods such as lean production, agile production and tools supporting their management processes in a global car supply chain. One of such tools is the loss reduction system (Kaizen Costing). The purpose of the paper is to present the issues of quality cost accounting which determine the level of quality costs to sales value, preventive costs, control and assessment costs, and cost of losses. On the basis of the loss cost account, the types of internal and external failure costs were determined in reference to the cost components that affect the losses and should be subject to the improvement process within the Kaizen Costing system. In the surveyed enterprises, they implemented the quality management system based on the IATF 16949 standard but they use different management accounting systems as they do not have the same owners. Moreover, their quality management systems are mature enough to be able to consciously assess the existing situation in reference to loss cost and determine the necessary improvement actions for products that are already in the production and delivery phase to the customer. However, their IT systems only include the main internal failure costs in the costs of foundry and mechanical departments, and in the case of external failure costs these are costs of complaints and special transports. The cost of losses of individual products require additional calculations outside the system.
Keywords: Quality Costs Calculation; Loss Cost; Kaizen Costing.